A Third Space Research Methodology through the Metaphor of Mokshya - Gautam, Suresh; Luitel, Bal Chandra (Journal of Education and Research, 2013)
In this paper we argue that research paradigms arising from the Western Modern Worldview (WMW) orients research enterprise to serve metaphysics of presence (positive evidence), propositional, deductive and analytical genre and logics (Luitel, 2003), thereby privileging knowing as misappropriating local knowledge system. When WMW fails to understand the connectedness within the local worldviews they are alike the colonization. In many researches are taken for granted to put all in boxes creating a dualism of West (colonized) and Non-west (decolonized). However, it the dualism of West and rest hardly recognizes the multiple realities of local people. At the same time I argue that valuing local ways of thinking and being is must in research methodology. In so doing I envision Third Space Methodology where we can realize the importance of both West and Rest drawing from their best practices. Developing such a methodology allows all voices to be heard but gives precedence to the Indigenous/local voice. This is why we suggest a Third Space (Mokshya- an interest of emancipation) methodology through breaking the hierarchies of West and local. We use a metaphor of Mokshyaa describing Eastern (Hindu/Baudhhist /Jain/Sikhs) epistemic view to be ware from the colonial and decolonial parameters of research. DOI: http://dx.doi.org/10.3126/jer.v3i2.8400 Journal of Education and Research August 2013, Vol. 3, No. 2, pp. 96-116